Experimental assessment of dual-scale resin flow-deformation in composites processing. (September 2015) - Rouhi, Mohammad S.; Wysocki, Maciej; Larsson, Ragnar
Abstract: In this paper we are concerned with the assessment of sub-models within a two-phase continuum mechanical FE framework for process modeling of composites manufacturing. In particular, the framework considers the inclusion of two deformation dependent models describing resin flow related to: (1) meso-scale wetting and compaction of individual plies and (2) overall preform deformation and macroscopic Darcian flow. Using micro-mechanical modeling, we model the physics of these sub-processes in relation to the recently developed Out-Of-Autoclave (OOA) prepergs. The models are placed in context with a compression–relaxation experiment, employed to study the preform deformations considered separated from other sub-processes. Finally, calibrations and model validations are carried out against the relaxation experiment to relate the FE framework to the mechanical response of the preform. Therefore, using the above experiment, parameter values out of the literature and those estimated from micrographs gave a fair agreement between the simulation and experiments.